Economics - Chrystal (Oxford, 2015)
"Written to engage you with real world issues and questions in economics, this book provides up-to-date coverage of the financial crisis and its many subsequent implications, which are vital to understanding today's economic climate. Case studies help you to understand how economics works in practice, and to think critically"--Back cover.